2006
DOI: 10.1111/j.1365-2966.2006.10893.x
|View full text |Cite
|
Sign up to set email alerts
|

Pulsar braking indices, glitches and energy dissipation in neutron stars

Abstract: Almost all pulsars with anomalous positive measurements (corresponding to anomalous braking indices in the range 5 < |n| < 100), including all the pulsars with observed large glitches (ΔΩ/Ω > 10−7) as well as post‐glitch or interglitch measurements, obey the scaling between and glitch parameters originally noted in the Vela pulsar. Negative second derivative values can be understood in terms of glitches that were missed or remained unresolved. We discuss the glitch rates and a priori probabilities of positi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
56
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 40 publications
(121 reference statements)
4
56
2
Order By: Relevance
“…Finally, measurements of very large values of braking indices (Johnston and Galloway 1999) could be an indication of the closeness toḟ = 0 state associated with back bending. However, this might be explained in a more standard way, by the behavior connected with the glitch phenomena (Johnston and Galloway 1999;Alpar and Baykal 2006).…”
Section: Discussionmentioning
confidence: 97%
“…Finally, measurements of very large values of braking indices (Johnston and Galloway 1999) could be an indication of the closeness toḟ = 0 state associated with back bending. However, this might be explained in a more standard way, by the behavior connected with the glitch phenomena (Johnston and Galloway 1999;Alpar and Baykal 2006).…”
Section: Discussionmentioning
confidence: 97%
“…As discussed by Woods et al (2004), the negative sign of the fractional change of the pulse‐frequency derivative is unusual for large radio pulsar glitches. For large glitches, the fractional frequency change is Δν/ν > 10 −7 and the fractional pulse‐frequency derivative has the range (see also Alpar & Baykal 1994, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In general the effects can be due to various processes including precession [128,129], Tkachenko modes [130], superfluid vortex creep [25], superfluid turbulence [103], or changes in the magnetic field [101,110,131]. Timing noise is of interest for the current discussion as it has been suggested that glitches below the observational threshold may be the cause of timing noise [25,132] and of the measurement of anomalous breaking indices [133,134]. Janessen & Stappers [135] in fact showed that small glitches can account for part of the timing noise in PSR B1951+32, but not all of it, while Hobbs et al [131] claimed that for young pulsars with τ c < 10…”
Section: Timing Noisementioning
confidence: 99%